Cyclophilin A facilitates influenza B virus replication by stabilizing viral proteins - Huizi Li; Wenhui Fan; Jie Min; Xiaoyuan Bai; Wenxian Yang; Heqiao Li; Yuna Zhao; Runshan Lin; Xiaojuan Jia; Wenjun Liu; Lei Sun (iScience, 2023)
Summary: Influenza B circulates annually and causes substantial disease burden in humans. However, little is known about the infection mechanisms of influenza B virus (IBV). Here, we find that the host factor cyclophilin A (CypA) facilitates IBV replication by targeting IBV non-structural protein 1 (BNS1) and nucleoprotein (BNP). CypA promotes OTUD4-mediated K48-linked BNS1 deubiquitination to stabilize BNS1 by upregulating OTUD4 expression. Meanwhile, CypA and the E3 ligase MIB1 competitively interact with BNP to inhibit its proteasomal degradation. Moreover, cyclosporine A treatment or CypA R55A mutation results in an impaired function of CypA in IBV replication. Notably, BNP hijacks CypA into the nucleus to enhance the activity of viral ribonucleoprotein complexes by enhancing the interaction between BNP and IBV polymerase basic protein 1. Taken together, this study unveils the critical role of CypA in facilitating IBV replication, suggesting that CypA is a promising target for anti-IBV drug.